Development of low-fat protein-enriched coconut residue flour - Ramirez Danivic Jesus Navarro
A low fat protein-enriched coconut residue flour (PECRF) was developed using defatted residue flour as raw material. Defatting was done using a fat expeller and the fat content of the raw material was reduced from about 41.14% to 33.28%. There was also a decrease in moisture composition from 3.92% to 1.19%. However, protein increased from 7.46% to 7.87% due to the increase in the % solids. The established parameters employed in the enrichment of high-fat CRF were followed for the development of low-fat PECRF. Approximately 90% of low-fat PECRF was recovered for every 40 g of coconut residue flour used. Proximate analyses showed that the protein and fat content increased from 8 to 18% and 33.28 to 42.06% respectively. However, moisture content decreased from 1.19 to about 0.9%. Protein yield was found to be 15.24%. The low-fat PECRF possessed a light brown pigment, a powdery fingerfeel, and a characteristic burnt coconut odor.